Pola Pemahaman Misdinar Tentang Tugas dan Fungsinya dalam Perayaan Ekaristi - Girin Franca Wanda; Fransiskus Telaumbanua; Gregorius Verensius Era (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2017)
This paper describes the results of a study conducted in order to find out Pattern of the Mass Attendants’ Comprehension about their jobs and functions in the Eucharistic Celebration. The study was conducted at Santo Stefanus Church-station in Bukuan, Samarinda, from December 2015 to February 2016. The study used qualitative approach, and phenomenology analysis. The data gathering method was combination of observation, in-depth interviews and documentation. The results of the study showed that as a whole the Mass Attendants at Santo Stefanus Church-station in Bukuan had a good comprehension of their jobs and functions in the Eucharistic Celebration, with the so-called comprehension pattern of Experience-Learning. The Mass Attendants got the comprehension about their jobs and functions as Mass Attendants from the capacity development program in the forms of training and assignments in the Eucharistic Celebration. The result of this study also revealed that good comprehension about the jobs and functions of Mass Attendants, has significant influence on the implementation of Mass Attendants’ jobs in the Eucharistic Celebration. With the comprehension pattern of Experience-Learning, it was apparent that age as well as experience were visible factors that influenced the Mass Attendants’ comprehension about their jobs and functions as the Mass Attendants. Mass Attendants of the Primary School ages had different level of comprehension compared to Mass Attendants of the Secondary School ages. The Mass Attendants who were just joining the group had different comprehension compared to the Mass Attendants who had joined the group for a long time, whether they were of the Primary School ages or of the Secondary School ages. The differences could be detected from the differences in the implementation of their jobs at Church in the Eucharistic Celebration.